A picture of tariff protection across the World in 2004: MAcMap-HS6, Version 2 - Boumellassa, Houssein; Laborde Debucquet, David; Mitaritonna, Cristina (International Food Policy Research Institute, 2009)
MAcMap-HS6v2 is a comprehensive database providing detailed protection data at the 6 digit level of the harmonized system (HS6), i.e. more than 5000 products, for the year 2004. It includes ad valorem equivalents on MFN tariffs for 169 importing countries, as well as bilateral applied protection, together with preferential provisions for 220 partners. Specific and compound tariffs and tariff rate quotasdata are also provided, at the same level of detail. In this paper we present the methodology used for building this new database, paying attention to the consequences from such choices. We then provide evidence on the world applied protection in 2004. Finally we investigate variations in tariffs occurred between 2001 and 2004.